Unidentified house - Gordon, John C. (photographer):::Creator::::::::::::
View of an L-shaped ranch style house. On the left, chairs are on the patio, and on the right, the front door is visible. Planters line the walkway close to a sliding glass door and the front door. A paritial view of a circular planter with a shadow of a tree is visible.